2023
DOI: 10.1097/hjh.0000000000003547
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping masked hypertension: do not forget the night

Cesare Cuspidi,
Elisa Gherbesi,
Marijana Tadic

Abstract: guidelines for the management of arterial hypertension of the European Society of Hypertension, for the first time ever, it has come to our attention that cirrhosis was briefly mentioned in a table, with a recommendation to preferentially use beta-blockers to treat hypertension in these patients [6]. The authors did not elaborate on this point in the text, but we believe that the simple mention of cirrhosis in the guidelines is already a huge milestone. The rationale behind this is not clear because there is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…e appreciate Dr Cuspidi and colleagues for their kind suggestions for our study. They suggested that because isolated nocturnal hypertension is known to be associated with worse cardiovascular outcomes, it should be considered as a type of masked hypertension [1].…”
mentioning
confidence: 99%
“…e appreciate Dr Cuspidi and colleagues for their kind suggestions for our study. They suggested that because isolated nocturnal hypertension is known to be associated with worse cardiovascular outcomes, it should be considered as a type of masked hypertension [1].…”
mentioning
confidence: 99%